Manajemen Mutu Pendidikan dan Alternatif Pemecahan Dada SMP Negeri di Kecamatan Aru Selatan Kabupaten Kepulauan Aru - Rosina S. P. Soyem; Izaak Hendrik Wenno; Arnold Sahalessy (Jurnal Pendidikan Geografi Unpatti, 2025)
This study explores the dynamics of educational quality management within island contexts characterized by limited infrastructure, rich cultural heritage, and strong community social capital. The research focuses on identifying leadership patterns and social collaboration that shape the culture of quality in junior high schools across the Aru Selatan District, Maluku Islands. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving school principals, teachers, and school committees. The findings indicate that successful quality management is driven by transformational leadership integrating reflective values, community collaboration, and adaptation to geographic constraints. Community participation, regional policy support, and participatory practices serve as catalysts for strengthening school quality culture. The study contributes theoretically by extending transformational leadership into the context of island-based education